2009
DOI: 10.1002/mrm.22156
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of T2* heterogeneity in human brain white matter

Abstract: Recent in vivo MRI studies at 7.0 T have demonstrated extensive heterogeneity of T2* relaxation in white matter of the human brain. In order to study the origin of this heterogeneity, we performed T2* measurements at 1.5, 3.0, and 7.0 T in normal volunteers. Formalin-fixed brain tissue specimens were also studied using T2*-weighted MRI, histological staining, chemical analysis, and electron microscopy. We found that T2* relaxation rate (R2*=1/ T2*) in white matter in living human brain is linearly dependent on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
76
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 28 publications
(36 reference statements)
4
76
1
Order By: Relevance
“…Interpreting resonance frequency data directly remains challenging, given the presence of multiple contributing mechanisms. Nonetheless, when combined with other information such as T 2 * (33) and magnetization transfer contrast (34), these resonance frequency data could be used to extract microstructural information for use in various clinical and scientific applications (e.g., high-resolution fiber tracking).…”
Section: Discussionmentioning
confidence: 99%
“…Interpreting resonance frequency data directly remains challenging, given the presence of multiple contributing mechanisms. Nonetheless, when combined with other information such as T 2 * (33) and magnetization transfer contrast (34), these resonance frequency data could be used to extract microstructural information for use in various clinical and scientific applications (e.g., high-resolution fiber tracking).…”
Section: Discussionmentioning
confidence: 99%
“…Previously published work suggests that this is, at least in part, due to microscopic susceptibility effects in white matter associated with large concentrations of myelin. 63 The effects of bulk magnetic susceptibility on resonance frequency and other characteristics of the water resonance are often dependent on orientation relative to B 0 . Lee et al 64 demonstrated that rotating parallel white matter nerve bundles 90…”
Section: Discussionmentioning
confidence: 99%
“…This variability may refl ect distinct pathologic processes. Recent studies (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) of healthy brains both in vivo and postmortem suggest that magnetic susceptibility contrast may have a number of contributors, including myelin and both heme iron (deoxyhemoglobin) and nonheme iron. The tissue concentration of nonheme iron and myelin are particularly relevant to MS as they may be refl ective of the underlying disease process ( 21 ).…”
Section: Neuroradiology: High-field-strength Mr Imaging Of Chronic Mumentioning
confidence: 99%
“…We and others have done this in normal tissue for gray matter and WM ( 28,29 ). Despite the lack of these derived measures of tissue iron ( 12,20 ), have suggested that iron and myelin are the main compounds that contribute to the R2* and phase contrast in WM and cortical gray matter. In particular, in the iron extraction experiment, Fukunaga and colleagues ( 28 ) reported subtle signs of contrast reversal after iron extraction in postmortem brain tissue, suggesting a small opposing frequency shift caused by the remaining myelin.…”
Section: Neuroradiology: High-field-strength Mr Imaging Of Chronic Mumentioning
confidence: 99%